Melasma and Vitiligo in Brown Skin - Handog, Evangeline B.; Enriquez-Macarayo, Maria Juliet; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2017)
This book sheds new light on pigmentary disorders in people with brown skin. Brown skin encompasses many races and ethnicities. Due to migration, people with brown skin are seen almost everywhere in the world. A wide variety of pigmentary disorders exists among this population but the most disturbing and challenging are melasma and vitiligo This book covers these two disorders, among people of brown skin, from the epidemiology to management, in a detailed yet easy-to-read and easy-to-use style.
Part 1: 1. The Concept of Brown Skin -- 2. Prevalent Skin Disorders in Brown Skin -- Part 2. MELASMA IN BROWN SKIN -- 3. Definition, Incidence, Etiology of Melasma in Brown Skin -- 4. Pathogenesis of Melasma -- 5. Classification and Clinical Presentations of Melasma in Brown Skin -- 6. Diagnosis of Melasma in Brown Skin: Wood$1 (Bs Lamp, Dermoscopy, Confocal Microscopy -- 7. The Histopathology of Melasma in Brown Skin -- 8. The Scoring Aid:- MASI and Modified MASI -- 9. Differential Diagnosis -- 10. Melasma and Comorbidities -- 11. Melanogenesis and new signaling regulators for the treatment of melasma -- 12. Topical Agents in Melasma -- 13.Botanicals in Melasma -- 14. Oral Lightening Agents -- 15. Chemical Peeling for Melasma -- 16. The Role of Lasers and Light Devices for the Treatment of Melasma -- 17. Iontophoresis and Mesotherapy in Melasma -- 18. Quality of life in melasma -- Part 3 -- 19. Vitiligo: Definition, Incidence, Etiology -- 20. The Pathogenesis of Vitiligo -- 21. Vitiligo Classification and Clinical Presentations -- 22. Dermoscopy in vitiligo -- 23. The Histopathology of Vitiligo in Brown Skin -- 24. Differential Diagnosis of Vitiligo in Brown Skin -- 25. Comorbidities In Vitiligo -- 26. Topical Medications in Vitiligo -- 27. Oral Medications in Vitiligo -- 28. Vitiligo Management: Procedural Options -- 29 -- Phototherapy in Vitiligo -- 30. VITILIGO AND QUALITY OF LIFE -- Part 4 -- 31. Photoprotection in Brown Skin -- 32. Camouflage for Brown Skin with Melasma or Vitiligo -- 33. What$1 (Bs in the Pipeline for Melasma and Vitiligo.s
Keywords: Medicine; Dermatology; Medicine & Public Health; Dermatology